Gender-specific relationship between alcohol consumption and injury in the South Korean adults: A nationwide cross-sectional study. Issue 14 (April 2017) - Rha, Eun Young; Kim, Ho Jun; Han, Kyungdo; Park, Yongkyu; Yoo, Gyeol
Abstract : Abstract: Alcohol-related injuries have been concerned worldwide. However, there have been no large cross-sectional epidemiologic studies. The aim of this study was to investigate the association between alcohol and the prevalence of injury according to gender in a representative sample of the South Korean population. This cross-sectional study was based on data obtained in the Korea National Health and Nutrition Examination Survey from 2010 to 2012. In total, 15, 249 Korean adults (7128 men and 8112 women) aged 19 years or older were enrolled. Injury was defined as the incidence of an injury or intoxication within the year before completing the survey questionnaire. Univariate and multiple logistic regression analyses were conducted to analyze the relationship between alcohol consumption and the prevalence of injury. Heavy alcohol consumption and high-risk drinking were associated with a higher prevalence of injury in women (adjusted odds ratio [aOR] and corresponding 95% confidence interval [CI]: 2.48 [1.321, 4.656], 1.816 [1.136, 2.929], respectively), and Alcohol Use Disorders Identification Test (AUDIT) scores ≥20 were associated with a higher prevalence of injury in both men and women (aOR and 95% CI: 1.425 [1.004, 2.024] and 3.71 [2.067, 6.66], respectively). According to the AUDIT scores results, women who were injured reported significantly more high-risk drinking behaviors per month compared with those who were not injured. Gender disparities in the relationship between alcohol and the prevalence of injury were found. Indeed, future research using a prospective design should examine the causal relationship between alcohol consumption and the prevalence injury according to gender to confirm that alcohol is a risk factor for injury and to identify the possible mechanisms underlying this phenomenon.